Pengaruh Aromaterapi Lavender terhadap Intensitas Nyeri pada Pasien Pasca Operasi di Rumah Sakit Dustira Cimahi - Bangun, Argi Virgona; Nur'aeni, Susi (Jurusan Keperawatan FIKES UNSOED, 2013)
Lavender as aromatherapy give effect of relaxing and sedation. Research aimed to know the influence of lavender aromatherapy on pain intensity on major surgical post operative patient. This research used pre-experimental design with one group pretest-posttest design form. Sample in this research as many as 10 people by purposive sampling technique and data analysis by paired t-test. Statistical test result obtained p value 0,001. There is seen a significance difference of pain intensity before and after lavender aromatherapy provision. Suggestion for Dustira Hospital Cimahi, research could become input for Hospital to applied lavender aromatherapy provision on post operative patient. Lavender aromatherapy should be taught before surgery, and patients can be applied in patients after surgery.